Quality assessment of YUNYAO radio occultation data in the neutral atmosphere - X. Xu; W. Han; W. Han; J. Wang; Z. Gao; Z. Gao; F. Li; Y. Cheng; N. Fu; N. Fu (Atmospheric Measurement Techniques)
Global Navigation Satellite System (GNSS) radio occultation (RO) data are an important component of numerical weather prediction (NWP) systems. To incorporate more GNSS-RO data into NWP systems, commercial RO data have become an excellent option. Tianjin Yunyao Aerospace Technology Co., Ltd. (YUNYAO) plans to launch a meteorological constellation of 90 satellites equipped with GNSS-RO instruments, which will significantly increase the amount of GNSS-RO data in NWP systems. This study evaluates the quality of neutral atmospheric refractivity and bending angle profiles from YUNYAO satellites Y003 to Y010 during the period from 1 May to 31 July 2023. Compared with the refractivity and bending angle calculated from ERA5, the absolute values of the mean bias (MB) for YUNYAO refractivity and bending angle data are less than 1.54 % and 4.51 %, respectively, in the height range of 0 to 40 km and close to 0 between 4 and 40 km. The standard deviations (SDs) are below 3.35 % and 11.06 %, respectively, with variations in SDs among different GNSS satellites, especially in the lower troposphere and the stratosphere. Second, the refractivity error SD of YUNYAO RO data is estimated using the “three-cornered hat” (3CH) method and multiple data sets. In the pressure range of 1000–10 hPa, the refractivity error SD of YUNYAO RO data is below 2.53 %, and the differences in refractivity error SDs among different GNSS satellites do not exceed 0.52 %. Finally, compared to COSMIC-2 and Metop-C RO data, YUNYAO RO data exhibit consistent refractivity error SDs and are smaller within 300–50 hPa.